The Effect Of Noise On The Level of Concentration In Wood Cutting Workers In Arjasa District, Jember District - Waskito Setiaji; Adelia Handoko; Ulfa Elfiah (Journal of Agromedicine and Medical Sciences, 2021)
Disorders of concentration in workers can cause workplace accidents due to decreased ability to focus attention when working. The annual work accident rate is estimated at 250 million with 1.2 million people dead. One of the causes of disturbances in worker concentration is the physical factor in the form of noise. One of the high intensity noise is found in the wood cutting industry in Arjasa District, Jember. The aim of this study is to analyze the effect of noise on the concentration level in wood cutting workers in Arjasa District, Jember. This is an analytic observational research with cross sectional study. The respondents amounted to 32 people taken with purposive sampling. The measurement of noise was using a sound level meter. The measurement of concentration level using Trail Making Test (TMT) A and B. Concentration level measurement is done when the respondent has worked for 30 minute. The results of the study showed that the majority of respondents were aged between 25-28 years (28.1%) and had worked less than the same as 2 years (53.1%). The average noise intensity of the wood cutting area was 97.5 dB (A) and the loading and unloading area was 76.2 dB (A). Average noise intensity of the wood cutting area exceeds the noise threshold value. The level of concentration of workers in the wood cutting area is lower than the loading and unloading area workers. The results of data analysis using the independent t test indicate that there are differences in the mean TMT B score: TMT A between respondents who work in noisy and non-noisy environments (p=0,004). There was a noise effect on the concentration level in wood cutting workers in Arjasa District, Jember Regency. Keywords: Noise, concentration, wood cutting workers